Developing Foreign Language Proficiency Through Speech Leaning in Early Childhood - Sumartono (Universitas Pancasakti Tegal, 2010)
Childhood is generally regarded as the most cheerful phase in people life. Related to the language learning, in this period of time a child unconsciously learns how to speak his/her vernacular trough constant imitation and repetition of the utterances produced by the older people when they are speaking in their mother tongue language. This phenomenon takes place when the child is about six to eight years old. In the years after, a foreign language will be effectively taught, because they are supposed to be adult linguistically, which means that tha child is going to get ready to learn a new set of habits in speaking. Several characteristics of children as young learners of a foreign language should be considered as a guideline to decide several kinds of approach, methods, techniques, and models of foreign language teaching and learning to optimize their foreign language proficiency, considering that they have specific and unique characteristics contrasted to adult learners. To yield an intended result, appropriate, accurate and integrated materials involving pronounciation, vocabulary enrichment and sentence arrangement must be selected in such a way and adjusted to the learners’ needs. It’s not easy to achieve the intended purpose of the process due to several handicaps such as; lisping, slurring, stuttering, and cluttering.